How exercise can deteriorate the clinical course of an ARVC patient: a case report. Issue 11 (12th October 2021) - Lüsebrink, Enzo; Binzenhöfer, Leonhard; Brunner, Stefan; Hausleiter, Jörg; Massberg, Steffen; Orban, Martin; Kääb, Stefan
Abstract: Background : Arrhythmogenic right ventricular cardiomyopathy (ARVC)/dysplasia is a genetic disease characterized by fibro-adipose degeneration of ventricular myocardium. Initial clinical presentation is variable and ranges from asymptomatic cases to chronic heart failure and sudden cardiac death due to malignant arrhythmias. Case summary : Here, a 67-year-old male patient who started extensive physical training upon retirement and presented with ventricular tachycardia and progressive heart failure as a first sign of his disease. Arrhythmogenic right ventricular cardiomyopathy diagnosis was established according to the 2010 modified Task Force Criteria and supported by HRS/EHRA consensus-based genotyping. After initial discharge on optimal medical therapy and prophylactic implantable cardioverter-defibrillator implantation according to his individual ARVC risk score, the patient reported rapid decline in physical capacity on a regular follow-up 4 months later. To better understand the aetiology of his clinical deterioration, we performed stress echocardiography, coronary angiogram, and exercise right heart catheterization, which conclusively suggest impaired left ventricular filling secondary to right ventricular failure as a main cause of global circulatory failure. Discussion : The present case report focuses on relation of physical activity to disease onset and the concomitant advent of symptoms during exercise as well as a structured and guideline-aided diagnostic workup in ARVC and staged treatment options. Continuous ARVC centre-oriented re-assessment and treatment planning including lifestyle intervention, psychological support, medical, surgical, and interventional options are key elements of sustained long-term care for ARVC patients.